2016
DOI: 10.1073/pnas.1523116113
|View full text |Cite
|
Sign up to set email alerts
|

Acinetobacter baumannii phenylacetic acid metabolism influences infection outcome through a direct effect on neutrophil chemotaxis

Abstract: Innate cellular immune responses are a critical first-line defense against invading bacterial pathogens. Leukocyte migration from the bloodstream to a site of infection is mediated by chemotactic factors that are often host-derived. More recently, there has been a greater appreciation of the importance of bacterial factors driving neutrophil movement during infection. Here, we describe the development of a zebrafish infection model to study Acinetobacter baumannii pathogenesis. By using isogenic A. baumannii m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
101
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(105 citation statements)
references
References 46 publications
2
101
1
Order By: Relevance
“…Most interestingly, we show that light directly modulates metabolic pathways, such as the PAA catabolic pathway, which is repressed by blue light in strain ATCC 19606 in a BlsA-dependent manner. The paa genes encode proteins responsible for the metabolism of aromatic compounds and have been linked to virulence in A. baumannii (11,25) and other human pathogens (26). It would therefore be expected that repression of the PAA pathway by light would 7).…”
Section: Discussionmentioning
confidence: 99%
“…Most interestingly, we show that light directly modulates metabolic pathways, such as the PAA catabolic pathway, which is repressed by blue light in strain ATCC 19606 in a BlsA-dependent manner. The paa genes encode proteins responsible for the metabolism of aromatic compounds and have been linked to virulence in A. baumannii (11,25) and other human pathogens (26). It would therefore be expected that repression of the PAA pathway by light would 7).…”
Section: Discussionmentioning
confidence: 99%
“…Again, caution may be warranted in that the A. baumannii strain background studied was ATCC 17978, a lab-adapted strain which was highly virulent in zebrafish but is essentially avirulent in healthy mice with a normal immune system, suggesting differences between the zebrafish and murine models. The authors also found that bacterial phenylalanine production was critical to triggering neutrophil chemoattraction to the site of infection (81). The phenylalanine catabolic pathway degrades phenylalanine, and a key step in that pathway is the paaA gene.…”
Section: Models Of Infectionmentioning
confidence: 98%
“…In at least one study, however, virulence outcomes in C. elegans did not correlate with outcomes in mice, so caution is warranted in interpreting translatability of results in this model (80). Finally, a recent study described a model of Acinetobacter virulence in zebrafish larvae (81). In this model, mutant strains that had been shown to have attenuated virulence in mice also had attenuated virulence, and host defenses depended on neutrophil and macrophage uptake, suggesting commonalities between this invertebrate model and mice.…”
Section: Models Of Infectionmentioning
confidence: 99%
“…The otic vesicle (Figure 4D, white dashed outline) provides a useful, immune-privileged and isolated site for testing neutrophil recruitment in zebrafish 9 . To test the ability of zebrafish neutrophils to respond to standard chemoattractants, 100 nM of fMLP and LTB4 were microinjected into the otic vesicles of 2 dpf zebrafish embryos (Figure 4F, J), using the microstructured channel device (Figure 1G) to stabilize embryos in the lateral orientation.…”
Section: Representative Resultsmentioning
confidence: 99%